The Spanish of Costa Rica - Cartín de Guier, Estrella (2013)
Early studies on the subject. Don Carlos Gagini (Dictionary of Costa Rican terms). Major contributions: Arturo Agüero, Víctor Arroyo, Víctor Sánchez, Miguel Ángel Quesada. Features of the Spanish in Costa Rica, which without being exclusive in our linguistic variety, are nevertheless of frequent use and shape the identity of the Spanish in Costa Rica. Markings of these features in the fields of phonetics, morphosyntax and vocabulary. In the field of phonetics for example we have the “seseo” (special employment of the “s”), the semiconsonant “y” (yeismo), the loss of hiatus, the apicoalveolar pronunciation of the “t” in the cluster “tr”. At the morphological level we have the diminutive endings “icoica”, intense reduplication of the diminutive and the superlative. The use of “vos” in the vocabulary, Costa Rican lexical terms not used in Spain. Spanish terms with special meaning in Costa Rica.